Estudio de factibilidad para la creación de una empresa productora y comercializadora de calzado por inyección al corte en Bogotá (2019)
A feasibility study was carried out in order to determine the feasibility of a shoe production and marketing company by injection to the cut, since it has an innovative and quality process having differentiating characteristics with the other products of its same sector. The location of this project is focused on the city of Bogotá, covering all the localities that can be focal points of consumption, reaching those that cover stratum 2,3 and 4, being a product focused on women and girls. Thanks to the study carried out and the results obtained, it was possible to identify the investment and the capital demanded to start with this project, which gives us the feasibility of the project, where we find that the internal rate of opportunity is 19.85%, a VPN of $ 422,252,670 , internal rate of return of 54%, cost benefit ratio of 2.77, being a viable project.